Analisis Strategi Pemenangan Partai Demokrasi Indonesia Perjuangan Dan Realisasi Target Pemenangan Ganjar Pranowo – Taj Yasin Maimoen Pada Pemilihan Umum Gubernur Dan Wakil Gubernur Jawa Tengah Tahun 2018 - Aulia - Adriansyah; Turtiantoro - - (Journal of Politic and Government Studies, 2020)
Researchers reviewed the winning strategy used by PDIP to win Ganjar Pranowo and Taj Yasin Maimoen in Central Java Pilgub 2018. In this election, PDIP emerged as a coalition party by holding PPP to seize the seat of Governor and deputy governor of Central Java. It is interesting to research because the previous Pilgub PDIP always appear without a coalition. This research uses a qualitative descriptive method by which the author wants to describe the actual situation and then conduct an analysis in depth with the aim to know in detail the winning strategy used by PDIP in Central Java Pilgub in 2018. Data is obtained through interviews with PDIP cadres who are in the team of winnings and also through supporting documents obtained from the journal and the Internet. The winning strategy used by PDIP in Central Java Pilgub is to conduct political campaign strategies, positioning strategies or figure protrusion, time base strategy, Community approach strategy and general strategy. The strategy proved to be a potent win for Ganjar Pranowo and Taj Yasin Maimoen in Central Java Governor General election, 2018.